أثر تطبيق نظام التصنيع الرشيق على تخفيض التكاليف البيئية: دراسة استطلاعية في معاونية السمنت الشمالية - خالص حسن يوسف الناصر (PROSPECTIVE RESEARCHES, 2023)
Environmental pollution is not a new problem for organizations, but the new is increasing of variety in pollution nowadays. The responsibility of the industrial sector in environmental pollution is a great one comparing to other sectors. Under multiple types of waste and the high cost of pollution, it has become imperative for the governments to find solutions and appropriate tools that control the causes of waste, reduce the cost of pollution and sustain the environment. Accordingly, advanced manufacturing systems have emerged. One of these advanced systems is the Lean Manufacturing System (LMS) that focuses mainly on removing waste regularly by using a set of tools such as Kaizen. Thus, a strong relationship between environmental improvement and LMS is created and this what the researcher is trying to study. The research aims to determine the impact of the application of LMS on environmental costs and its role in supporting sustainable development. The research hypothesis is that the application of LMS assists organizations in removing or reducing waste and hence reducing the cost of environmental pollution. The research concluded with a set of conclusions. The most important one is that the traditional manufacturing systems create waste and do not take into consideration the environmental impact of manufacturing processes. The researcher to recommended organizations apply the LMS as it is considered a driver for sustainable improvement of the environment and the reduction of environmental pollution costs.